SCENARIO PLANNING DEVELOPMENT FOR PUBLIC TRANSPORTATION IN JAKARTA TO ACHIEVE NET ZERO EMISSION - Rizky Ramadhan, Muhammad
Indonesia is one of the countries that participated in the Paris Agreement, the international pact concerned with reducing global warming growth. Indonesia has also targeted to achieve Net Zero Emission (NZE) in 2060 or earlier. Reducing the emissions produced can be done in many sectors; one is through the transportation sector. This study is taken part in Jakarta, the capital city of Indonesia. As one of the cities of World's Worst Cities for Traffic Jams in 2020, Jakarta produced a high number of emissions. This research was conducted to identify the challenges and plausible scenarios for public transportation in Jakarta in the upcoming ten years to achieve net zero emissions. In this study, the authors conducted industry analysis using PESTEL and supported with data collection, consisting of literature review and interview. The interviews were conducted with several respondents from public transportation providers who comprehensively understand public transportation and the implementation of net zero emissions in their respective firms. The interview aims to capture what steps have been taken, the challenges, and the driving forces that have high impact and uncertainty, which may drive the implementation of net zero emissions in their respective firms. The interview results then used to be the primary material for scenario analysis to achieve net zero emission for public transportation in Jakarta. The interview activities captured four high impact driving forces: 1) Economic, 2) Technological, 3) Legal and 4) Political. Besides that, there is four high uncertainty driving forces: 1) Socio-culture, 2) Economic, 3) Political, and 4) Legal. Instead of choosing which top two factors have the highest impact and uncertainty, the author built a scenario based on all those factors. Considering that all factors have interconnection, the implementation will not run well if we take out one from the group. Otherwise, the key focal issue in this study is “What steps need to be taken to achieve Net Zero-Emissions in the next ten years?”. The developed scenario in this study is conducted in the form of transformative scenarios. There are five scenarios, and the sequence of scenarios is implemented based on urgency to achieve the ideal situation according to the interconnection analysis of each factor above. The combination of all of these created five scenarios, namely 1) Gridlock and Pollution, 2) Stopping at Red Light, 3) Green Light to Go, 4) Getting There, and 5) Green and Connected. Therefore, it is expected that the public transportation providers cooperate with the government, regulators, and firms related to their operation to achieve net zero emission in 2032.